Refining the Baveno VI elastography criteria for the definition of compensated advanced chronic liver disease - Papatheodoridi, Margarita; Hiriart, Jean Baptiste; Lupsor-Platon, Monica; Bronte, Fabrizio; Boursier, Jerome; Elshaarawy, Omar; Marra, Fabio; Thiele, Maja; Markakis, Georgios; Payance, Audrey; Brodkin, Edgar; Castera, Laurent; et al. (Journal of hepatology, 2021)
Background - The Baveno VI consensus proposed a dual liver stiffness (LS) by transient elastography threshold of <10 and >15 kPa for excluding and diagnosing compensated advanced chronic liver disease (cACLD) in the absence of other clinical signs. Herein, we aimed to validate these criteria in a real-world multicentre study. - Methods - We included 5,648 patients (mean age 51 ± 13 years, 53% males) from 10 European liver centres who had a liver biopsy and LS measurement within 6 months. We included patients with chronic hepatitis C (n = 2,913, 52%), non-alcoholic fatty liver disease (NAFLD, n = 1,073, 19%), alcohol-related liver disease (ALD, n = 946, 17%) or chronic hepatitis B (n = 716, 13%). cACLD was defined as fibrosis stage ≥F3. - Results - Overall, 3,606 (66%) and 987 (18%) patients had LS <10 and >15 kPa, respectively, while cACLD was histologically confirmed in 1,772 (31%) patients. The cut-offs of <10 and >15 kPa showed 75% sensitivity and 96% specificity to exclude and diagnose cACLD, respectively. Examining the ROC curve, a more optimal dual cut-off at <7 and >12 kPa, with 91% sensitivity and 92% specificity for excluding and diagnosing cACLD (AUC 0.87; 95% CI 0.86-0.88; p <0.001) was derived. Specifically, for ALD and NAFLD, a low cut-off of 8 kPa can be used (sensitivity=93%). For the unclassified patients, we derived a risk model based on common patient characteristics with better discrimination than LS alone (AUC 0.74 vs. 0.69; p <0.001). - Conclusions - Instead of the Baveno VI proposed <10 and >15 kPa dual cut-offs, we found that the <8 kPa (or <7 kPa for viral hepatitis) and >12 kPa dual cut-offs have better diagnostic accuracy in cACLD. - Lay summary - The term compensated advanced chronic liver disease (cACLD) was introduced in 2015 to describe the spectrum of advanced fibrosis and cirrhosis in asymptomatic patients. It was also suggested that cACLD could be diagnosed or ruled out based on specific liver stiffness values, which can be non-invasively measured by transient elastography. Herein, we assessed the suggested cut-off values and identified alternative values that offered better overall accuracy for diagnosing or ruling out cACLD.
Online 9 December 2020
Gesehen am 16.06.2021